9.5=(k/9)

Simple and best practice solution for 9.5=(k/9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9.5=(k/9) equation:



9.5=(k/9)
We move all terms to the left:
9.5-((k/9))=0
We add all the numbers together, and all the variables
-((+k/9))+9.5=0
We multiply all the terms by the denominator
-((+k+(9.5)*9))=0
We calculate terms in parentheses: -((+k+(9.5)*9)), so:
(+k+(9.5)*9)
We calculate terms in parentheses: +(+k+(9.5)*9), so:
+k+(9.5)*9
determiningTheFunctionDomain k+(9.5)*9
We add all the numbers together, and all the variables
k+85.5
Back to the equation:
+(k+85.5)
We get rid of parentheses
k+85.5
Back to the equation:
-(k+85.5)
We get rid of parentheses
-k-85.5=0
We add all the numbers together, and all the variables
-1k-85.5=0
We move all terms containing k to the left, all other terms to the right
-k=85.5
k=85.5/-1
k=-85+0.5/1

See similar equations:

| 4(2x+3)-8x=2x-12 | | 23-5x=114x=30 | | 177+5x=33-3x | | 5/3+3y=6y−2/15 | | x/17=17 | | 7=z-5 | | 4(2x+3)=8x=2x-12 | | 21-6/7x=-6/7+21 | | f/6+8=-3 | | f/6+8=-6 | | 24=9t-3 | | (11r+3)+(6r+6)=8 | | x/24=8 | | 2x/3+4=3 | | a/2+11=73 | | 7(c-16)=-105 | | 1/2t-4(2+1)=20 | | 3/5c=9 | | 25+07=46-13x | | 14w=2w+12 | | 3b+2b=10= | | X+4=-x=-4 | | -3(n+5)=3 | | 6x^2-174=0 | | (11r+3)+6r+6)=8 | | 4/3=2.3(t+7/3) | | 8g+11=3 | | 4(9-3x)-x=0 | | 1/3(3x-12)=2x-1/3 | | 0.2x+1.4=3.5x | | 8-7/10h=6-1/5h | | 6r+7=18r+11 |

Equations solver categories